Development of Appropriate Power Distribution Design for Can-Sized Satellite (CANSAT) - Marubin, Devina Cristine; Sim Sy Yi (Journal of Advanced Industrial Technology and Application, 2021)
Can-sized satellite (canSAT) is a small satellite that is used for educational purpose. CanSAT offer student to build their satellites with their creativity which make the learning process more effective. In Malaysia, SiswaSAT is held by the Malaysia Space Agency for students in different categories to participate and build their satellites according to rules set and it should be a low-cost project. CanSAT can be divided into few parts which are communication system, onboard data acquisition, ground control station and power system. The power system is one of the important and heaviest subsystems, it needed to supply power, but weight and size are one of the main concerned as the canSAT should not exceed the required weight and selecting power supply that is matched with the overall power budget that has small size and lightweight is challenging. Therefore, the power supply selection should consider this detail. The power distribution design should be able to supply an appropriate amount of current and voltage to the components according to their specification. This study aims to develop and test the proposed prototype which is named ScoreSAT able to provide data and have enough power supply for the whole operation. Therefore, an initiative to develop the appropriate power distribution design for canSAT is taken to overcome the problem of the power system. Moreover, each subsystem needs to be tested by obtaining the results from the onboard data acquisition and transmit the data using the communication system before integrating into the power system. ScoreSAT prototype needs to carry the system that is mounted inside, thus the space inside the prototype needs to be fully utilized for the whole system to fit in. ScoreSAT completes the mission by obtaining data acquisition during the operation